AGR3 Regulates Airway Epithelial Junctions in Patients with Frequent Exacerbations of COPD - Ye, Rui; Wang, Cuihong; Sun, Pengbo; Bai, Shuang; Zhao, Li (Frontiers in Pharmacology, 2021)
Background: The mechanisms underlying differences in the susceptibility to chronic obstructive pulmonary disease (COPD) exacerbations between patients are not well understood. Recent studies have showed that the frequency of COPD exacerbations is related to specific protein expression in lung tissue. Anterior gradient 3 (AGR3) is expressed in airway epithelial cells in the lung and proteomic analysis revealed that its expression is decreased in patients with frequent COPD exacerbations. Moreover, the loss of epithelial integrity might facilitate trans-epithelial permeability of pathogens in such patients. This study was performed to determine that AGR3 protein play a role in COPD frequency exacerbators. Methods: Human lung tissues were collected from current-smoking patients (Control; n=15) as well as patients with infrequent COPD exacerbators (IFCOPD; n=18) and frequent COPD exacerbators (FCOPD; n=8). While AGR3 protein expression was measured by immunohistochemistry and western blotting, AGR mRNA expression was determined by real time quantitative polymerase chain reaction (RT-qPCR). Furthermore, adherent junctions (AJs) and tight junctions (TJs) protein expression in human lung tissues were measured by immunohistochemistry. The effect of cigarette smoke extract (CSE) on AJ and TJ protein and mRNA expression in BEAS-2B cells was assessed by western blotting and RT-qPCR. In addition, the effect of AGR3 overexpression and knockdown on AJ and TJ protein expression was determined. Results: AGR3 was mainly expressed in the airway epithelium and AGR3-positive products were localized in the cytoplasm. Western blotting and RT-qPCR results showed that AGR3 protein (p=0.009) and mRNA (p=0.04) expression in the FCOPD group was significantly lower than that in the IFCOPD group. Moreover, E-cadherin, occludin, and zonula occludens-1 (ZO-1) expression was lower in the FCOPD group than in the IFCOPD group. The protein and mRNA expression of E-cadherin, occludin, and ZO-1 was decreased within 24 h post-CSE exposure. AGR3 overexpression rescued CSE-induced downregulation of E-cadherin, occludin, and ZO-1. Conclusions: Difference in AGR3 expression in the lung tissue might be correlated with increased susceptibility to COPD exacerbation. AGR3 can prevent CSE-induced downregulation of E-cadherin, occludin, and ZO-1 in airway epithelial cells. Loss of AGR3 might promote viral and bacterial infection and induce immune inflammation to increase COPD exacerbation.